DEVELOPMENT OF PROBLEM-BASED LEARNING TOOLS ON BIODIVERSITY THAT ACCOMMODATE MARIND TRIBE'S MEDICINAL PLANT GARDEN TO IMPROVE CRITICAL THINKING SKILLS AND ENVIRONMENTAL LITERACY OF AGRICULTURAL VOCATIONAL SCHOOL STUDENTS. - Fakhrudin; Suhartini; Paidi (Postgraduate, University of Mataram, 2025)
This study aims to develop a problem-based learning (PBL) tool for biodiversity that integrates the Marind Tribe's medicinal plant garden as a contextual learning resource in an agricultural vocational school. The development was conducted using the Research and Development (R&D) method with the 4D model (Define, Design, Develop, Disseminate). The results showed that the developed learning tool was highly valid in terms of content, construct, and integration with the local context. The practicality of the tool was reflected in the ease of implementation, clarity of instructions, and high student engagement. The effectiveness of the tool was demonstrated by a significant increase in students' critical thinking scores based on N-gain analysis, as well as increased environmental literacy and cultural awareness. The local context adopted from the Marind Tribe's medicinal plant garden successfully fostered an appreciation for ecological values and cultural wisdom. This study provides an important contribution to the development of learning tools that combine scientific, cultural, and contextual approaches as a form of ecopedagogy implementation. It is recommended that a similar approach be implemented more widely across educational institutions, taking into account their respective local cultural contexts. Further research is recommended to evaluate the long-term impact on environmental conservation and strengthening local cultural identity.